Characterization of structural and immunological properties of specific domains of Friend ecotropic and dual-tropic murine leukemia virus gp70s. - Pinter, A (1984)
A detailed comparison of the gp70 proteins of cloned ecotropic Friend murine leukemia virus (FLV) and dual-tropic Friend mink focus-forming virus (FrMCF) was performed by analyzing the structural and immunological properties of amino- and carboxy-terminal domains of these molecules generated upon controlled trypsinization. The two gp70s gave characteristic fragmentation patterns; the amino-terminal fragments of FrMCF gp70 were smaller than the corresponding fragments of FLV and contained a trypsin site which resulted in a 19,000-dalton amino-terminal fragment not observed for FLV, whereas both molecules yielded an identically sized carboxy-terminal fragment. All amino-terminal fragments of both gp70 molecules contained an endo H-sensitive oligosaccharide chain; for FrMCF, a second endo H-sensitive carbohydrate was present as well at a carboxy-terminal site for approximately 50% of the molecules. Several aspects of the disulfide interactions of the two gp70s were conserved; in both cases the carboxy-terminal fragments were disulfide bonded to p15(E), there were no disulfide bonds between amino- and carboxy-terminal fragments, and the amino-terminal fragments exhibited a significant increase in mobility upon analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis under nonreducing conditions. Analysis of the immunoreactivity of the different domains of the proteins by immunoprecipitation of the fragments with antisera prepared against xenotropic murine leukemia virus and feline leukemia virus gp70s indicated major differences in antigenicity for the amino-terminal domains of FLV and FrMCF gp70, whereas the carboxy-terminal domains were immunologically conserved. Similar analyses with antibodies specific for p15(E) and Pr15(E) demonstrate that these components are conserved as well. These data provide direct evidence that p15(E) and the C-terminal gp70 domain of FrMCF gp70 are related to the corresponding regions of the ecotropic FLV parent and indicate that the acquisition of MCF-specific properties is due to the replacement of the ecotropic amino-terminal gp70 domain with sequences related to those of xenotropic gp70s.